AFN as Bricolage: Towards an alternative notion of “alterity” as “hybridity” - Xu, Chenjia (The International Journal of Sociology of Agriculture and Food, 2025)
The alterity of alternative food networks (AFN) is increasingly difficult to define, given the multiplicity of their ‘hybrid practices’ that intersect both the ‘alternative’ and the ‘conventional’. This article proposes the framework of bricolage to address the alterity-hybridity tension. Building on the post-binary construal that sees both the alternative and the conventional as hybrid collectives, bricolage registers the alterity of AFN and their transformative potential in the mode in which resources and values are hybridised. With the ethnographic account of how a famers’ market in Beijing ‘makes do’ with the available resources in its multi-layered environment, and subsequently ‘skews’ and subverts the ‘conventional’ from within, the article demonstrates that it is through the distinct modus operandi of hybridity that the prospects of doing food otherwise are opened.